(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
Semantic field analysis is a crucial aspect of lexicological research, aiming to explore the interconnectedness of words within a specific conceptual domain. This article delves into the significance of semantic fields in understanding language structure and meaning. It discusses the theoretical foundations of semantic field theory, its practical applications in lexicography, and its role in language acquisition and cognitive linguistics. Furthermore, the article examines the challenges and debates surrounding semantic field analysis, providing a comprehensive overview of its current state in lexicological research. By shedding light on the complexities and nuances of semantic fields, this article aims to contribute to the ongoing discourse on the nature of lexical meaning and its implications for linguistic theory and practice.